Benchmarking w controllingu zaopatrzenia - Kowalak, Robert (Benchmarking in Supply Controlling, 2005)
This article is devoted to the application of benchmarking in controlling of supply. The benchmarking in sphere of supply permits to apply the best, optimum permissive solutions to reach the best results for the whole enterprise. Benchmarking can also give an answer to the question that solutions are leading not only in branch but also among different enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 320-326